Candy Consumption Patterns, Effects on Health, and Behavioral Strategies to Promote Moderation: Summary Report of a Roundtable Discussion,. Issue 1 (7th January 2015) - Duyff, Roberta L; Birch, Leann L; Byrd-Bredbenner, Carol; Johnson, Susan L; Mattes, Richard D; Murphy, Mary M; Nicklas, Theresa A; Rollins, Brandi Y; Wansink, Brian
ABSTRACT: Nearly all Americans (97%) report eating candy at least once per year; yet, on a given day, only approximately one-fourth of the US population aged ≥2 y consumes candy. Among all Americans, candy contributes a relatively small proportion of calories, added sugars, and saturated fat to the total diet, and recent research suggests that current levels of candy consumption are not associated with risk of weight gain and cardiovascular disease in children and adults. Providing guidance for the consumption of candy in moderation requires an understanding of various behavioral health-related factors that influence candy consumption. A roundtable of behavioral nutrition experts, researchers, and nutrition educators met to discuss recent data on intakes of candy, health outcomes associated with usual candy intake, and the impact of behavioral strategies, including restriction, education, and environmental awareness, on modifying eating behaviors to achieve moderate intakes of candy. Restricting access to palatable foods, whether self-imposed or by parental control, may have potentially negative consequences. Techniques and insight into how to adopt "moderation" in candy consumption, from effective parental practices to environmental strategies that facilitate behavior change without a high degree of effort, were identified as important next steps toward sustainable dietary guidance related to the role of candy and other treats in a healthy lifestyle.